Air pollution and infant mortality: Evidence from the expansion of natural gas infrastructure - Resul Cesur; Erdal Tekin; Aydogan Ulker (Institute for the Study of Labor (IZA), 2013)
One of the consequences of rapid economic growth and industrialization in the developing world has been deterioration in environmental conditions and air quality. While air pollution is a serious threat to health in most developing countries, environmental regulations are rare and the determination to address the problem is weak due to ongoing pressures to sustain robust economic growth. Under these constraints, natural gas, as a clean, abundant, and highly-efficient source of energy, has emerged as an increasingly attractive source of fuel, which could address some of the environmental and health challenges faced by these countries without undermining their economies. In this paper, we examine the impact of air pollution on infant mortality in Turkey using variation across provinces and over time in the adoption of natural gas as a cleaner fuel. Our results indicate that the expansion of natural gas infrastructure has caused a significant decrease in the rate of infant mortality in Turkey. In particular, a one-percentage point increase in the rate of subscriptions to natural gas services would cause the infant mortality rate to decline by 4 percent, which could result in 348 infant lives saved in 2011 alone. These results are robust to a large number of specifications. Finally, we use supplemental data on total particulate matter and sulfur dioxide to produce direct estimates of the effects of these pollutants on infant mortality using natural gas expansion as an instrument. Our elasticity estimates from the instrumental variable analysis are 1.25 for particulate matter and 0.63 for sulfur dioxide.
Keywords: I0; I12; I15; I18; O10; O13; Q42; Q48; Q53; 330; air pollution; infant mortality; environment; natural gas; coal; Turkey